Structural Equation Modelling (SEM) Approach On Inappropriate Construction Equipment Delay Factors - B. Indhu; K. Yogeswari (Salehan Institute of Higher Education, 2021)
The advancement of construction equipment is a trend in the construction industry, with numerous benefits. However, using inappropriate construction equipment causes delays in construction projects, affecting the firm's reputation. A number of research studies on overall delay have been conducted globally. Even so, there is a lack of research on construction delays caused by inappropriate construction equipment. The aim of this paper is to investigate the inappropriate construction equipment delay factors and their effects on the firm's reputation. Based on the issues identified in the focus group interviews and the literature survey, a questionnaire survey was conducted to assess the impact of these factors on the progress of Indian construction projects. The primary constraint was that all 300 responses were collected in person from construction professionals to avoid lethargic responses that could skew the results. Pearson correlation coefficients were used to determine the positive strength of each factor's relationship. A t-test was used to see if there was a significant difference between the respondents' firm categories. Structural Equation Modeling (SEM) was used to validate the effective relationship between the causes of delays due to inappropriate construction equipment and its impact on company's reputation. All of the factors examined by the SEM analysis evidenced that the inappropriate construction equipment factors are correlated among themselves and combined to impact the reputation of the company. Recommendations are made to overcome the inappropriate equipment delay factors. Doi: 10.28991/cej-2021-03091717 Full Text: PDF